2020
DOI: 10.1021/acsami.0c11435
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive and Flexible Dopamine–Graphene Hybrid Electronic Textile Yarn for Sensitive and Selective NO2 Detection

Abstract: Graphene-based electronic textile (e-textile) gas sensors have been developed for detecting hazardous NO 2 gas. For the e-textile gas sensor, electrical conductivity is a critical factor because it directly affects its sensitivity. To obtain a highly conductive e-textile, biomolecules have been used for gluing the graphene to the textile surface, though there remain areas to improve, such as poor conductivity and flexibility. Herein, we have developed a dopamine−graphene hybrid electronic textile yarn (DGY) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…In SEM images, both the RGO/F BLG /CYs before and after washing possessed numerous wrinkles and ripples on their surface, exhibiting no significant difference between both of them (Figure S8, Supporting Information). 39 The washed RGO/F BLG /CYs were respectively exposed to 10 ppm NO 2 for 6 min, and their electrical currents were measured by the I−V analyzer. Figure S7b shows the electrical currents of the RGO/F BLG / CYs exposed to 10 ppm NO 2 with respect to the washing cycle.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In SEM images, both the RGO/F BLG /CYs before and after washing possessed numerous wrinkles and ripples on their surface, exhibiting no significant difference between both of them (Figure S8, Supporting Information). 39 The washed RGO/F BLG /CYs were respectively exposed to 10 ppm NO 2 for 6 min, and their electrical currents were measured by the I−V analyzer. Figure S7b shows the electrical currents of the RGO/F BLG / CYs exposed to 10 ppm NO 2 with respect to the washing cycle.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Accordingly, what type of sensor exhibit more improved conductivity depends on the number of graphene flakes attached to each sensor (Figure S5, Supporting Information). We measured the response characteristics of the e-textile yarns by exposing them to a constant concentration (100 ppm) of NO 2 for 15 min and then plotted the changes in electrical current (Δ I = I – I 0 , where I 0 and I denote the electrical current before and after exposure to the target analyte, respectively) (Figure a). The plots showed that all Δ I s for the five types of e-textile yarns exponentially increased for 15 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic textiles (e-textiles) have attracted signi cant attention in various applications, including chemical gas sensors (Lee et To fabricate the graphene e-textiles, graphene has been attempted to coat on various 1-dimensional textiles (e.g., cotton yarn, nylon-6 yarn, and polyester yarn) (Lee et al 2021b; Lee et al 2020;Yun et al 2013; Ju Yun et al 2015). According to the literature, graphene e-textiles exhibit mechanical exibility, washability, and the ability to sense toxic gases (Lee et al 2020; Lee et al 2021b). Thus, graphene etextiles have the potential to be used as wearable sensors for detecting toxic gases and even for monitoring human health from their breath.…”
Section: Introductionmentioning
confidence: 99%